Identification of carbon‐hydrogen complexes in n‐ and p‐type silicon. Issue 10 (11th July 2016) - Stübner, Ronald; Kolkovsky, Vladimir; Scheffler, Leopold; Weber, Joerg
Abstract: The origin of several deep traps E42, E90, E262, and H180 in hydrogenated n ‐type and p ‐type FZ and CZ Si is investigated. Comparing the depth profiles of these defects in samples with different C, O, H, and shallow donor (acceptor) concentrations we conclude that they belong to carbon‐hydrogen‐related defects consisting of one C and one H atom. The similar annealing behavior and identical depth profiles of E42 and E262 correlate them with two different charge states of the same defect. From a comparison with earlier calculations we attribute E42 to the double acceptor and E262 to the single acceptor state of the CH1AB complex. In good agreement with the results of previous studies E90 is assigned to the acceptor state of the CH1BC complex. Our preliminary Laplace DLTS studies on SiGe with a Ge content <5% show different local Ge environments for E90 and H180 in the nearest and second‐nearest neighborhood. We interpret this as an indication for a different origin of these defects. After annealing the samples under reverse bias at 320 K another CH‐related defect (CHB ) can be detected by Laplace DLTS in n ‐type Si. Previously, this defect was often wrongly assigned to the single donor state of CH1BC . The field dependence of the emission rate of CHB identifies the level as a single donor state. However, the depth distribution of CHB differs clearly from that of E90. Our results on the carbon‐hydrogen complex give a conclusive explanation of previously reported controversial experimental data. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)